Fisheries in the Pacific : The challenges of governance and sustainability - Simonne Pauwels (pacific-credo Publications, 2016)
Fisheries in the Pacific: The Challenges of Governance and Sustainability is a multidisciplinary book, which examines various aspects of coastal and oceanic fisheries in Pacific waters. These interrelated fisheries sectors are critical for regional food security and also represent a reserve of food resources for the rest of the world. The introduction and eight chapters highlight that both these sectors raise major economic and ecological issues while revealing significant social changes, political asymmetries and alliances, geostrategic rationales, developments in legislation, customary dynamics, and conservation challenges. Through complementary approaches and interpretations of both quantitative and qualitative data, this book aims to contribute to a better understanding of the current situation of fisheries in the Pacific. It also responds to the compelling need to establish a constructive and ongoing dialogue on the matter between social scientists and environmental scientists, based in Europe and in the Pacific Islands, and between these experts and the various stakeholders and policy-making institutions involved in the Pacific region.